2008
DOI: 10.1111/j.1742-6723.2008.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing triage consistency in Australian emergency departments: The Emergency Triage Education Kit

Abstract: All scenarios that showed good levels of agreement have been included in the Emergency Triage Education Kit and are recommended for testing purposes; those that showed moderate agreement have been incorporated for teaching purposes. Both scenario sets are accompanied by explanatory notes that link the decision outcome to the Australasian College for Emergency Medicine Guidelines on the Implementation of the Australasian Triage Scale. Future analysis of the scenarios is required to identify how task-related fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 23 publications
(62 reference statements)
2
53
1
2
Order By: Relevance
“…6 A recent review of the ATS concluded that 'the ATS per se is insufficient to ensure acceptable inter-rater reliability, particularly during busy periods in the ED, given the over-emphasis of the ATS on key outcomes'. 7 The inter-rater reliability of the ATS for mental health patients in ED is particularly inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent review of the ATS concluded that 'the ATS per se is insufficient to ensure acceptable inter-rater reliability, particularly during busy periods in the ED, given the over-emphasis of the ATS on key outcomes'. 7 The inter-rater reliability of the ATS for mental health patients in ED is particularly inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gerdtz et al [6,7] found that although the improvement has not been significant, marked improvement has been obtained. In fact, the reliability of the ATS increased from a fair reliability coeffi cient of Dilley et al [2] in 1998 to moderate reliability coeffi cient of Gerdtz et al [7] in 2008, indicating that revision was considerably effective. Therefore, the ATS needs to be enhanced through the years and improved in order to reach almost perfect reliability (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Gerdtz et al [6] 2007 Adult NN Scenario Inter Κuw (0.38) Australia Gerdtz et al [7] 2008 Adult NN Scenario Inter Κuw (0.41) Australia Table 1. Studies on the reliability of the ATS * NN: nurse-nurse; ** Inter: inter-rater reliability; Intra: intra-rater reliability; *** Kuw: Un-weighted kappa (coeffi cient).…”
Section: Australiamentioning
confidence: 99%
See 2 more Smart Citations